2015
DOI: 10.1177/1074248415591698
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Therapy for the Treatment of Hypertension-Induced Cardiac Hypertrophy and Fibrosis

Abstract: These findings suggest a role for epigenetic modifications in contributing to the profibrotic and hypertrophic changes evident during disease progression. Therapeutic intervention with 5-aza demonstrated favorable effects highlighting the potential use of this epigenetic modifier as a treatment option for cardiac pathologies associated with hypertrophy and fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 45 publications
2
56
0
1
Order By: Relevance
“…In vivo gene transfer of these transcription factors after MI attenuated fibrosis and cardiac dysfunction [179]. Interestingly, it was recently shown that hypertrophy and fibrosis could also be treated with the administration of epigenetic drugs, such as the DNA methylation inhibitor 5-azacytidine or the previously mentioned HDAC inhibitors [180]. …”
Section: Clinical and Translational Perspectivesmentioning
confidence: 99%
“…In vivo gene transfer of these transcription factors after MI attenuated fibrosis and cardiac dysfunction [179]. Interestingly, it was recently shown that hypertrophy and fibrosis could also be treated with the administration of epigenetic drugs, such as the DNA methylation inhibitor 5-azacytidine or the previously mentioned HDAC inhibitors [180]. …”
Section: Clinical and Translational Perspectivesmentioning
confidence: 99%
“…Transcriptional inhibition of NF-κB, a redox-sensitive transcription factor, could inactivate antiapoptotic proteins [73] as may epigenetic modifications of myofibroblast gene expression and survival [74]. A DNA methylation inhibitor has shown promise in the treatment of hypertension-induced hypertrophy with fibrosis [75]. …”
Section: Cardioprotective Strategiesmentioning
confidence: 99%
“…Так, відмічено покращення кількох ехокардіографічних показників, пов'язаних із гіпертрофією і діастолічною дисфункцією міокарда у щурів, яким вводили 5-азаци-тидин. Ці дані набули пояснення внаслідок досліджень серцевих фібробластів шлуноч-ків серця in vitro, при яких було вивлено зменшення вмісту колагену I і III, α-актину гладеньких м'язів [50].…”
Section: можливості профілактики та лікування аг через епігенетичні вunclassified